2009
DOI: 10.1001/archoto.2008.537
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Nasal Cycle in Daily Activity by Remote Evaluation of Nasal Sound

Abstract: With the help of the OR program, we detected the nasal cycles in all of the volunteers, and the periods were not less than 30 minutes or more than 2.5 hours. Because the data collection period was long and the patient compliance was maximal, we believe that the results in the study are more reliable and natural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…The increase in cycle duration during sleep was also significant in the previously cited study by Kimura et al Physical rest and fewer environmental factors may be suggested as the principal reasons for this. Elsewhere, cycle durations ranging from 19 minutes to > 10 hours are reported in the literature . Similarly large interindividual differences were also noted in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in cycle duration during sleep was also significant in the previously cited study by Kimura et al Physical rest and fewer environmental factors may be suggested as the principal reasons for this. Elsewhere, cycle durations ranging from 19 minutes to > 10 hours are reported in the literature . Similarly large interindividual differences were also noted in our study.…”
Section: Discussionsupporting
confidence: 89%
“…There are many studies in the literature supporting the idea that 80% of the population exhibits a phenomenon called nasal cycle (2,10 studies researching the reciprocity of nasal airflow, reported a lower range varying from 21% to 39%. Tahamiler et al reported a cyclic nasal airflow change in only 21% of 52 volunteers (11). Gilbert showed bilateral rhythmicity in only 2 of 16 healthy subjects and bilateral reciprocity in 7 out of 16 volunteers by using autocorrelation as a measure of rhythmicity (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Tahamiler et al nasal cycle was investigated at every 30 minutes over a period of 12 hours on 4 different days in the same week and measured at 96 times for each subject. They used the Odiosoft-Rhino (OR) software program and detected nasal cycles in all healthy volunteers at different days (11). In the second study, Kern reported that any individual is not confined to a specific type of non-cycle nose as measurements were performed some months apart on one subject who manifested two different `types' at the different points in time.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the temporally discrete airflow methods is in their accuracy, but when used to characterize an ongoing cycle one needs to have subjects return for measurement at high frequency, and moreover, such discrete measurements cannot be applied in sleep. In turn, continuous measurements can be made using thermal [ 75 ] and auditory sensors [ 83 ], or using small pressure sensors at the far end of tubes nestled at the nasal opening. Whereas several such efforts have been extended [ 84 86 ], a commercial device for assessing the nasal cycle over time remains an expensive option in a large-scale medical device (e.g., http://www.orl.biofonia.com/rcs_gene/medical_equipment/Leaflet_RHINO-SYS_GAESaudiotest_ENG.pdf ), and the aforementioned studies did not provide details that would allow the interested scientist to build their own simple tool.…”
Section: Introductionmentioning
confidence: 99%